Not all kidney cysts are created equal: a distinct renal cystogenic mechanism in tuberous sclerosis complex (TSC) - Soleimani, Manoocher (Frontiers in Physiology, 2023)
Tuberous Sclerosis Complex (TSC) is an autosomal dominant genetic disease caused by mutations in either TSC1 or TSC2 genes. Approximately, two million individuals suffer from this disorder worldwide. TSC1 and TSC2 code for the proteins harmartin and tuberin, respectively, which form a complex that regulates the mechanistic target of rapamycin complex 1 (mTORC1) and prevents uncontrollable cell growth. In the kidney, TSC presents with the enlargement of benign tumors (angiomyolipomas) and cysts whose presence eventually causes kidney failure. The factors promoting cyst formation and tumor growth in TSC are poorly understood.Recent studies on kidney cysts in various mouse models of TSC, including mice with principal cell-or pericyte-specific inactivation of TSC1 or TSC2, have identified a unique cystogenic mechanism. These studies demonstrate the development of numerous cortical cysts that are predominantly comprised of hyperproliferating A-intercalated (A-IC) cells that express both TSC1 and TSC2. An analogous cellular phenotype in cystic epithelium is observed in both humans with TSC and in TSC2 +/-mice, confirming a similar kidney cystogenesis mechanism in TSC. This cellular phenotype profoundly contrasts with kidney cysts found in Autosomal Dominant Polycystic Kidney Disease (ADPKD), which do not show any notable evidence of A-IC cells participating in the cyst lining or expansion.RNA sequencing (RNA-Seq) and confirmatory expression studies demonstrate robust expression of Forkhead Box I1 (FOXI1) transcription factor and its downstream targets, including apical H + -ATPase and cytoplasmic carbonic anhydrase 2 (CAII), in the cyst epithelia of Tsc1 (or Tsc2) knockout (KO) mice, but not in Polycystic Kidney Disease (Pkd1) mutant mice. Deletion of FOXI1, which is vital to H + -ATPase expression and intercalated (IC) cell viability, completely inhibited mTORC1 activation and abrogated the cyst burden in the kidneys of Tsc1 KO mice. These results unequivocally demonstrate the critical role that FOXI1 and A-IC cells, along with H + -ATPase, play in TSC kidney cystogenesis. This review article will discuss the latest research into the causes of kidney cystogenesis in TSC with a focus on possible therapeutic options for this devastating disease.